2011
DOI: 10.1017/s0007114511003771
|View full text |Cite
|
Sign up to set email alerts
|

Marine n-3 fatty acids, atrial fibrillation and QT interval in haemodialysis patients

Abstract: Patients treated with haemodialysis are at high risk of sudden cardiac death (SCD) often caused by arrhythmias. Atrial fibrillation (AF) is frequent among haemodialysis patients and is associated with increased mortality. Prolonged QTc is a risk marker of ventricular arrhythmia and is thereby associated with SCD. Studies have suggested that n-3 PUFA may have an antiarrhythmic effect, but the exact mechanism is not clear. The aim of this study was to examine whether AF was associated with n-3 PUFA in plasma pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Particularly, supplements with a relatively higher amount of DHA (>1g/d) seemed to relate to a significant decreased risk of POAF and LOH after surgery, while did not for supplements with lower amount of DHA, suggesting that DHA may be the determinant for the potential preventative effect of fish oil for POAF. These findings are consistent with the results of recent cross-sectional [44] and cohort studies [45], [46], which suggested that lower serum content of DHA but not EPA was independently associated with increased risk of AF in humans. Although the exact mechanisms underlying the possible different effects of DHA and EPA on POAF are unknown, there is some evidence from studies in animals and humans [47], [48] which indicated that compare to EPA, DHA can favorably influence some physiological processes involved in AF pathogenesis in a more effective way, such as anti-inflammation and reduction of heart rate.…”
Section: Discussionsupporting
confidence: 92%
“…Particularly, supplements with a relatively higher amount of DHA (>1g/d) seemed to relate to a significant decreased risk of POAF and LOH after surgery, while did not for supplements with lower amount of DHA, suggesting that DHA may be the determinant for the potential preventative effect of fish oil for POAF. These findings are consistent with the results of recent cross-sectional [44] and cohort studies [45], [46], which suggested that lower serum content of DHA but not EPA was independently associated with increased risk of AF in humans. Although the exact mechanisms underlying the possible different effects of DHA and EPA on POAF are unknown, there is some evidence from studies in animals and humans [47], [48] which indicated that compare to EPA, DHA can favorably influence some physiological processes involved in AF pathogenesis in a more effective way, such as anti-inflammation and reduction of heart rate.…”
Section: Discussionsupporting
confidence: 92%
“…19 A recent publication from the Cardiovascular Health Study observed that plasma DHA, but not EPA, was correlated with lower AF incidence in a cohort of more than 3000 elderly Americans. 20 Similarly, Kirkegaard et al 21 found that plasma DHA, but not EPA, was associated with a lower incidence of AF in 300 hemodialysis patients with cardiovascular disease. Data from 2174 middle-aged men in the Kuopio ischemic heart disease risk factor study showed that serum DHA, but not EPA, was significantly inversely correlated with risk of AF.…”
Section: Observations Of the Dha Effect In Other Studiesmentioning
confidence: 95%
“…The same authors reported that there was no change in heart rate variability in haemodialyzed patients during 8 weeks of n-3 PUFA supplementation at a dosage of 1.7 g day -1 . 125 A recently published controlled study by Kirkegaard et al 126 showed an inverse association between the presence of arterial fibrillation and plasma DHA. This is very important because high risk of sudden cardiac death is often caused by arrhythmias.…”
Section: Pufas and Blood Pressure And Mortalitymentioning
confidence: 97%